The Influence Of Leading Sectors On Poverty Rate In The District Padang Lawas Utara - Khairul Kamal (Al-Makki Publisher, 2023)
Leading sectors are expected to be able to overcome the problem of poverty-level economic development. The purpose of this study is to find out which sectors are the leading sectors in North Padang Lawas Regency and to find out how the growth of these leading sectors influences the poverty rate in North Padang Lawas Regency. The type of data used in this study is secondary data obtained from the Central Bureau of Statistics of North Padang Lawas Regency and the Central Bureau of Statistics of North Sumatra Province. The results of this study are based on Location Quotient (LQ) and Growth Ratio Model (MRP) analysis, there are three leading sectors in North Padang Lawas Regency, namely agriculture, animal husbandry, and forestry; processing industry sector; as well as the construction sector. Based on the results of multiple linear regression analysis simultaneously leading sectors have a significant influence on the poverty rate in North Padang Lawas Regency. Partially, the agricultural, livestock, and forestry sectors have a positive and significant effect on the level of poverty. Partially, the manufacturing sector has a negative and significant effect on the poverty rate. Partially, the construction sector has a negative and insignificant effect on the poverty rate